Cystic fibrosis transmembrane conductance regulator-related metabolic syndrome/cystic fibrosis screen positive, inconclusive diagnosis (CRMS/CFSPID). Issue 3 (September 2021) - Sinha, Aditi; Southern, Kevin W.
Newborn bloodspot screening (NBS) for cystic fibrosis (CF) is an effective strategy for the early recognition of infants with a CF diagnosis. Some infants with a positive NBS result for CF have an inconclusive diagnosis and evidence suggests the number of these infants is increasing, as more extensive gene analysis is integrated into screening protocols. There is an internationally agreed, but complex, designation for infants with an unclear diagnosis after a positive screening result: cystic fibrosis transmembrane conductance regulator (CFTR)-related metabolic syndrome/cystic fibrosis screen positive, inconclusive diagnosis (CRMS/CFSPID). Infants with a CRMS/CFSPID designation have no clinical evidence of disease and do not meet the criteria for a CF diagnosis, but the NBS result indicates some risk of developing CF or a CFTR-related disorder. In this review, we describe the accurate designation of these and reflect on emerging management pathways, with particular attention given to clear and consistent communication. Educational aims: To clarify the definition of the global harmonised designation: cystic fibrosis transmembrane conductance regulator-related metabolic syndrome (CRMS)/cystic fibrosis screen positive, inconclusive diagnosis (CFSPID). To understand what impact a CRMS/CFSPID result has for the patient and their family. There is an internationally agreed, but complex, designation for infants with an unclear diagnosis after a positive screening result: CRMS/CFSPID. The majority of CRMS/CFSPID infants remain well and do not convert to a diagnosis of CF. https://bit.ly/3mtpJTu